INVERTED INTERNAL LIMITING MEMBRANE FLAP TECHNIQUE FOR MACULAR HOLES IN HIGH MYOPIA WITH AXIAL LENGTH ≥30 mm. Issue 9 (September 2016) - Oleñik, Andrea; Rios, José; Mateo, Carlos
Abstract : Purpose: To evaluate the closure rate of macular holes in highly myopic eyes treated with the inverted internal limiting membrane flap technique. Methods: Retrospective study in 33 consecutive patients (33 eyes) with a myopic macular hole (axial length ≥30 mm) and no associated macular retinoschisis, undergoing 23-gauge pars plana vitrectomy combined with the inverted internal limiting membrane flap technique. Results: Mean initial logarithm of the minimum angle of resolution best-corrected visual acuity was 0.59 (range, 0.22–1.8) (Snellen fraction, 20/80). At the 1-month postoperative control visit, the macular hole was closed in all patients. Reopening of the hole occurred in 2 patients. Visual acuity improved in 13 patients (39.4%): final mean ETDRS (Early Treatment Diabetic Retinopathy Study) improvement was +80 letters, and logarithm of the minimum angle of resolution was 0.4 (20/50). Staphyloma with macular involvement was present in all patients. Dissociated optic nerve fiber layer was observed in 25 patients (75.7%) and was absent in 2 (6.1%); in the remaining 6 patients, the layer could not be assessed. Gliosis was found in 14 patients (42.4%). Conclusion: Vitrectomy plus the inverted internal limiting membrane flap technique was effective for treating macular holes in eyes with axial length ≥30 mm and no associated retinoschisis. Abstract : Vitrectomy with the inverted internal limiting membrane flap technique was effective for treating macular holes in a clinical series of 33 highly myopic patients (axial length ≥30 mm) with no associated retinoschisis.